Pelatihan Peningkatan Kualitas Kopi untuk Mencapai Keunggulan Kompetitif di Desa Babadan, Kecamatan Ngajum, Kabupaten Malang - Meirezaldi, Onni; Sulasmiyati, Sri; Fahrudi, Agung Nugroho Lutfi Imam; Nuzula, Nila Firdausi (Journal of Applied Community Engagement, 2022)
Coffee has transformed into a lifestyle for their lovers, and they can sip it anytime when they want. Coffee connoisseurs are hunting for local coffee. They are no longer looking for well-known brands that have been present for a long time. This situation opens up an opportunity for the local coffee industry to evolve. Located on the slopes of Mount Kawi, the Babadan village area settles the proper location to carry out this strategy. The agroforestry system combines the production of pinewood plants and coffee plants. Improving the quality of coffee plants is an ongoing effort to improve the quality or quality of coffee bean products. Increasing the advantages of coffee beans can be done through several approaches: intensification of coffee plants, rehabilitation of coffee plants, and rejuvenation of coffee plants. The output of this approach is expected to increase the income potential of local coffee farmers. Through this community service activity, training and assistance to local farmers to improve farmers' knowledge and skills about good and correct coffee plant care.